Effect of Turmeric (Curcuma domestica Vahl.) Extract on Broiler Blood Cholesterol Levels - Muliani, Hirawati (JURNAL SAINS DAN MATEMATIKA, 2015)
This study aimed to determine the effect of turmeric extract on blood cholesterol levels of broiler chickens. The material used in this study were 24 male broiler chickens type of CP 707 and acclimated for 1 week. The chickens were then grouped into 4 treatment groups with 6 replicates in each group. The treatments were T0: without treated (control), T1: given the turmeric extract 200 mg/kg/day; T2: given the turmeric extract 400 mg/kg/day; T3: given the turmeric extract 600 mg/kg/day. The Turmeric extract was given in capsule form and treatment was in 6 weeks. The main parameters measured were the chicken blood cholesterol levels. The supporting parameters measured were body weight and feed intake. The data obtained were analyzed by variance analysis with a completely randomized design and Duncan test. The results showed that turmeric extract had no effect on blood cholesterol levels broiler.